2022
DOI: 10.1111/jfbc.14259
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review on modulation of SIRT1 signaling pathways in the immune system of COVID ‐19 patients by phytotherapeutic melatonin and epigallocatechin‐3‐gallate

Abstract: SARS‐CoV‐2 infection has now become the world's most significant health hazard, with the World Health Organization declaring a pandemic on March 11, 2020. COVID‐19 enters the lungs through angiotensin‐converting enzyme 2 (ACE2) receptors, alters various signaling pathways, and causes immune cells to overproduce cytokines, resulting in mucosal inflammation, lung damage, and multiple organ failure in COVID‐19 patients. Although several antiviral medications have been effective in managing the virus, they have no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 165 publications
0
7
0
Order By: Relevance
“…Although not absorbed in the GI tract to a great extent, polyphenols have become highlighted for their impacts on gut health, particularly due to the secondary metabolites that form from their interaction with the microbiota [ 47 ]. There are initial indications that the antioxidant and anti-inflammatory actions of melatonin may work together with select polyphenols (e.g., resveratrol, epigallocatechin 3-gallate) for therapeutic indications [ 48 , 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Scientific Mechanismsmentioning
confidence: 99%
“…Although not absorbed in the GI tract to a great extent, polyphenols have become highlighted for their impacts on gut health, particularly due to the secondary metabolites that form from their interaction with the microbiota [ 47 ]. There are initial indications that the antioxidant and anti-inflammatory actions of melatonin may work together with select polyphenols (e.g., resveratrol, epigallocatechin 3-gallate) for therapeutic indications [ 48 , 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Scientific Mechanismsmentioning
confidence: 99%
“…ACE-2 prevents LPS-induced ARDS by blocking MAPKs and NF-κB signaling pathway and also protect against lung inflammation [7]. Epigallocatechin-3-gallate in C. sinensis increased sirtuins proteins which leads to decrease in pro-inflammatory gene transcription and NF-kB, protecting organisms from oxidative stress in autoimmune, respiratory, and cardiovascular diseases [55].…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with [ 60 ] who detected significantly decreased SIRT1 expression in COVID-19 patients, which was negatively correlated with p53, IL1-β, and TNF. [ 16 ] showed that SIRT1 can reduce inflammation in COVID-19 patients. [ 75 ] found that SIRT1 inactivation was linked to COVID-19 severity and its low level served as a predictor of COVID-19 that was not under control.…”
Section: Discussionmentioning
confidence: 99%
“…Sirtuins also provide defense against viral infections [ 15 ]. SIRT1 can suppress NF-κB [ 16 ], as well as bind to ACE2 promotor enhancing its expression [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%